Effect of inclusion of fish protein hydrolysate in diet for european whitefish (coregonus lavaretus linnaeus, 1758) juveniles on their hematological parameters - Shakhova Eugenia; Mezenova Olga; Romanenko Natalia; Agafonova Svetlana; Volkov Vladimir; Kalinina Natalia; Pyanov Dmitry (BIO Web of Conferences, 2023)
Prior studies have measured the effects on the Growth and Survival of supplementing fish diets with fish protein hydrolysate (FPH) as an alternative protein source. Initial results have suggested a positive impact on fish health and this study aimed to investigate specifically the impact of a 5% substitution of FPH on European Whitefish juveniles hematological parameters. A 56-day manual feeding trial was conducted on two triplicate groups of 500 fish, consulting of a control diet group and 5% FPH diet group. A feeding rate of 3% of total biomass was applied with feeding being carried out three times a day. The higher concentration of hemoglobin (60.73±3.55 g/L vs. 51.47±2.52 g/L), color index (1.62±0.15 vs. 1.23±0,07) and mean corpuscular hemoglobin (56.64±3.49 g/L vs. 45.75±2.11 g/L), as well as the lower level of oxyphilic normoblasts (1.33±0.26 % vs. 2.08±0.32 %) in the blood of fish in the experimental group, indicate active metabolic processes occurring in their bodies and better oxygen supply to their tissues. The significantly higher concentration of total protein in the blood serum (48.29±1.48 g/L vs. 35.35±1.43 g/L) of this group of fish suggests better food assimilation in their organism. The hematological data obtained during the study indicate the positive influence of the fish protein hydrolysate on the fish organism.